Do substantial BMI reduction episodes among Swedish schoolchildren have any impact on their final height?. (28th February 2018) - Nilsen, Bente B.; Yngve, Agneta; Werner, Bo
Abstract: Aim: This study investigated whether substantial body mass index (BMI) reductions in Swedish schoolchildren aged seven years to 19 years, caused by disease, healthy or unhealthy behaviour, had any impact on their final height. Methods: We used height and weight data on 6572 subjects from two nationally representative longitudinal samples of Swedish children born in 1973 and 1981. These provided information on their final height and any BMI reduction episodes. Results: Of the 6572 subjects (50.9% boys), among individuals with information on final height, 1118 had a BMI reduction of 5% and <10%, and 346 had at least one substantial BMI reduction of 10% or more. On a group level, there was no statistically significant difference in the final height of individuals with BMI reductions of 10% or more and those without. The findings were independent of age and the subject's BMI at the start of the reduction episode. However, there were a number of cases where a substantial BMI reduction probably had an impact on the subject's final height. Conclusion: Our study found no evidence that a substantial BMI reduction had any impact on final height on a group level, but further analyses of specific case studies are necessary to determine whether substantial BMI reduction might have an impact on final height.